Neuroplasticity associated with tactile language communication in a deaf-blind subject - Obretenova, Souzana; Halko, Mark A.; Plow, Ela B.; Pascual-Leone, Alvaro; Merabet, Lotfi B. (Frontiers in Human Neuroscience, 2010)
A longstanding debate in cognitive neuroscience pertains to the innate nature of language development and the underlying factors that determine this faculty. We explored the neural correlates associated with language processing in a unique individual who is early blind, congenitally deaf, and possesses a high level of language function. Using functional magnetic resonance imaging (fMRI), we compared the neural networks associated with the tactile reading of words presented in Braille, Print on Palm (POP), and a haptic form of American Sign Language (haptic ASL or hASL). With all three modes of tactile communication, indentifying words was associated with robust activation within occipital cortical regions as well as posterior superior temporal and inferior frontal language areas (lateralized within the left hemisphere). In a normally sighted and hearing interpreter, identifying words through hASL was associated with left-lateralized activation of inferior frontal language areas however robust occipital cortex activation was not observed. Diffusion tensor imaging (DTI)-based tractography revealed differences consistent with enhanced occipital-temporal connectivity in the deaf-blind subject. Our results demonstrate that in the case of early onset of both visual and auditory deprivation, tactile-based communication is associated with an extensive cortical network implicating occipital as well as posterior superior temporal and frontal associated language areas. The cortical areas activated in this deaf-blind subject are consistent with characteristic cortical regions previously implicated with language. Finally, the resilience of language function within the context of early and combined visual and auditory deprivation may be related to enhanced connectivity between relevant cortical areas. <input id="gwProxy" type="hidden"><!--Session data--></input><input id="jsProxy" onclick="jsCall();" type="hidden" />